2020
DOI: 10.1177/2331216520980299
|View full text |Cite
|
Sign up to set email alerts
|

Extended High Frequencies Provide Both Spectral and Temporal Information to Improve Speech-in-Speech Recognition

Abstract: Several studies have demonstrated that extended high frequencies (EHFs; >8 kHz) in speech are not only audible but also have some utility for speech recognition, including for speech-in-speech recognition when maskers are facing away from the listener. However, the contribution of EHF spectral versus temporal information to speech recognition is unknown. Here, we show that access to EHF temporal information improved speech-in-speech recognition relative to speech bandlimited at 8 kHz but that additional acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 36 publications
(54 reference statements)
3
23
0
Order By: Relevance
“…Our results demonstrated the importance of EHF information in speech recognition and therefore stress the importance of EHF hearing. This study and much published research found correlations between EHF hearing and speech perception in challenging conditions (Badri et al 2011; Yeend et al 2017, 2019; Motlagh Zadeh et al 2019; Trine & Monson 2020). Therefore, audiologists should consider adding at least 1 EHF (e.g., 12 kHz) to the standard test frequencies in audiometry.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Our results demonstrated the importance of EHF information in speech recognition and therefore stress the importance of EHF hearing. This study and much published research found correlations between EHF hearing and speech perception in challenging conditions (Badri et al 2011; Yeend et al 2017, 2019; Motlagh Zadeh et al 2019; Trine & Monson 2020). Therefore, audiologists should consider adding at least 1 EHF (e.g., 12 kHz) to the standard test frequencies in audiometry.…”
Section: Discussionsupporting
confidence: 69%
“…However, over the past two decades, compelling evidence has come to light that extended high-frequency (EHF; frequencies >8 kHz) cues: (1) are richly available in speech (Moore et al 2008; Monson et al 2012), (2) are important in front-back sound localization (Best et al 2005), (3) play a role in sound quality assessment (Moore & Tan 2003; Monson et al 2011, 2014), (4) improve phoneme identification when lower-frequency information is absent or degraded (Lippmann 1996; Vitela et al 2015), (5) enhance speech recognition in noise when target and masker talkers are spatially separated (Levy et al 2015) or have mismatched head orientations (Monson et al 2019; Trine & Monson 2020), and from recent studies, (6) improve speech recognition in noise in diotic listening conditions (Motlagh Zadeh et al 2019, 2020). Thus, EHFs are relevant, particularly in challenging listening conditions such as recognizing speech-in-noise.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of low-pass filtering EHFs on speech-in-noise recognition have been equivocal as well. Trine and Monson (2020) showed that access to EHF (up to 20 kHz) temporal information improved speech-in-speech recognition relative to speech bandlimited to 8 kHz. In addition, the performance was sensitive to masker head orientation, similar to a previous study (Monson et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…45 Recent work highlights the importance of auditory sensitivity in the EHFs while listening in background noise. [58][59][60][61] These results suggest that EHF audiometry may be of importance in a standard clinical test battery. Beyond behavioral measures of hearing function, physiological assessments such as otoacoustic emissions, ABRs, and electrocochleography provide objective measurements of hearing function and should be considered in a test battery to assess a patient for regenerative therapy.…”
Section: Conclusion and Thoughts On The Future Of Audiologic Testingmentioning
confidence: 84%